Complexities in understanding antimicrobial resistance across domesticated animal, human, and environmental systems. Issue 1 (29th March 2019) - Graham, David W.; Bergeron, Gilles; Bourassa, Megan W.; Dickson, James; Gomes, Filomena; Howe, Adina; Kahn, Laura H.; Morley, Paul S.; Scott, H. Morgan; Simjee, Shabbir; Singer, Randall S.; Smith, Tara C.; et al.
Abstract: Antimicrobial resistance (AMR) is a significant threat to both human and animal health. The spread of AMR bacteria and genes across systems can occur through a myriad of pathways, both related and unrelated to agriculture, including via wastewater, soils, manure applications, direct exchange between humans and animals, and food exposure. Tracing origins and drivers of AMR bacteria and genes is challenging due to the array of contexts and the complexity of interactions overlapping health practice, microbiology, genetics, applied science and engineering, as well as social and human factors. Critically assessing the diverse and sometimes contradictory AMR literature is a valuable step in identifying tractable mitigation options to stem AMR spread. In this article we review research on the nonfoodborne spread of AMR, with a focus on domesticated animals and the environment and possible exposures to humans. Attention is especially placed on delineating possible sources and causes of AMR bacterial phenotypes, including underpinning the genetics important to human and animal health. Abstract : Antimicrobial resistance (AMR) is a significant threat to both human and animal health. Our article reviews research on the nonfoodborne spread of AMR with a focus on domesticated animals and the environment, and possible exposure risks to humans. Attention is especially placed on delineating possible sources and causes of AMR bacterial phenotypes, including underpinning genetics important to human and animal health.